Lady Valor [videorecording (DVD)] : the Kristin Beck story - Beck, Kristin, 1966-; Herzog, Mark; Herzog, Mark; Orabona, Sandrine (Wolfe Video, 2014)
Former U.S. Navy SEAL Christopher Beck embarks on a new mission as Kristin Beck. Kristin's journey in search of the American ideals that she protected has a whole new meaning as she lives her life truthfully as a transgender woman. After a lifetime of service, Kristin has learned that her fight for life, liberty, and the pursuit of happiness did not end on the battlefield.